Patients’ Satisfaction with Pharmacy Services in a Secondary Health Care Facility in Benin City - Odili , V. U.; Ihenyen , A.O.; Okhawere , M.I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Patient satisfaction is a measure of how pharmacy services meet the needs of patients. It is one way of assessing the outcome of pharmacy services and identifying gaps. The aim of the study was to evaluate patients’ satisfaction with pharmacy services in a secondary health facility in Benin City. A descriptive cross-sectional survey was conducted in the outpatient Pharmacy Department of Central Hospital, Benin City. A two-part structured questionnaire was used to assess respondents’ level of satisfaction with pharmacy services. Overall, the respondents had a mean satisfaction score of 4.00 + 0.82, implying that their level of satisfaction with pharmacy services was very good. The respondents were very satisfied with the explanatory skills and courtesy of the pharmacists with scores of 4.44+ 0.66 and 4.33+ 0.72 respectively. They were also very satisfied with the pharmacy location (4.25+ 0.64). However, the respondents were relatively less satisfied with the waiting area, the length of time spent waiting for their drugs and the pharmacist’s ability to advise them about their medicine related problems all with the following scores 3.15 + 1.18, 3.43 + 1.25 and 3.70 + 0.83, respectively. The study showed that most of the respondents were satisfied with the pharmacy services they received at the facility.